PENERAPAN AJARAN TASAWUF-TAREKAT DI PONDOK PERSULUKAN (PONSLUK) DARUSSOUFIYAH DESA HUTA LOMBANG KECAMATAN PADANGSIDIMPUAN TENGGARA (Suatu Tinjauan Aplikatif Metodologis) Oleh : - Hasibuan, Armyn (TAZKIR: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2014)
AbstractThis Collective research is descriptive research qualitative aim to see to near from applying of teaching of tasawuf-tarekat in The Maisonette of Persulukan (Ponsluk) Darussoufiyah Countryside of Huta Lombang District of Padangsidimpuan South-East as one of the institute education of religious nonformal continual in guiding all " Salikin", both for have old man age and also relatively young. As for instrument gathering of data in this research are observation, interview deef and follow as participant. Besides meeting khalifah and some of its pupil which looked into can give clarification and information.The Maisonette of Persulukan (Ponsluk) Darussoufiyah Countryside of Huta Lombang District of Padangsidimpuan South-East teaching of tasawuf-tarekat taught and applied with science about tasawuf-tarekat like practicing or maqomat to implentation, elementary teaching and indepth way of sufism to the seasonal and mandah with interest ahead give study about bases of faith of God, fiqh, behavior, tasawuf step by step and transformasiExcellence of maisonette of Persulukan (Ponsluk), on personality, science and seriousness of Sheikh H. Muhammad Fauzi Siregar, where character, demeanour and his compatible characteristic very as counsellor (Mursyid). That thing are supported by its ability explain indepth coherent ketarekatan everyday way of living with simple life concept. Socialization conducted by Sheikh H. Muhammad Fauzi Siregar by lifting to all pupil become Khalifah Tawajuh and of Khalifah Tarekat. If no in this place, hence activity of religious service ritual, Tawajuh, Recitation, Khataman and other will remain to walk with existence of khalifah or it to proxymity.Keyword : Ponsluk, tasawuf-tarekat dan Darussoufiyah